Antifouling and antimicrobial biomaterials: an overview. Issue 4 (April 2017) - Francolini, Iolanda; Vuotto, Claudia; Piozzi, Antonella; Donelli, Gianfranco
Abstract : The use of implantable medical devices is a common and indispensable part of medical care for both diagnostic and therapeutic purposes. However, as side effect, the implant of medical devices quite often leads to the occurrence of difficult‐to‐treat infections, as a consequence of the colonization of their abiotic surfaces by biofilm‐growing microorganisms increasingly resistant to antimicrobial therapies. A promising strategy to combat device‐related infections is based on anti‐infective biomaterials that either repel microbes, so they cannot attach to the device surfaces, or kill them in the surrounding areas. In general, such biomaterials are characterized by antifouling coatings, exhibiting low adhesion or even repellent properties towards microorganisms, or antimicrobial coatings, able to kill microbes approaching the surface. In this light, the present overview will address the development in the last two decades of antifouling and antimicrobial biomaterials designed to potentially limit the initial stages of microbial adhesion, as well as the microbial growth and biofilm formation on medical device surfaces.